Effect of the structure and morphology of natural, synthetic and post-processed graphites on their dispersibility and electronic properties - Kozhemyakina, Nina; Eigler, Siegfried; Inayat, Alexandra; Schwieger, Wilhelm; Hirsch, Andreas; Dinnebier, Robert E. (Fullerenes Nanotubes and Carbon Nanostructures, 2013)
Twenty-two different graphite grades of the families natural, synthetic, intercalated, expanded, amorphous, and turbostratic graphite, as well as platelets and activated carbon, were analyzed on their dispersibility in N-methylpyrrolidone, cyclohexylpyrrolidone and water-sodium cholate solution. They were characterized for their properties (grain size, density, purity, surface area, pH in water) and morphology. Thermogravimetric analysis, Raman spectroscopy studies, and electrical conductivity measurements were also used. XRPD followed by a Rietveld refinement provided information on the amounts of the rhombohedral (3R) and hexagonal (2H) phases for the crystalline part of the material and the interlayer distances. The properties of graphites favoring better dispersibility are: small grain size and bulk density, neutral pH in water. The electrical conductivity in inversely proportional to the Raman D-band intensity and is highest for the graphites with shortest interlayer spacing. The D-, G- and 2D-bands in the Raman spectra of graphites are in an exponential relation. © 2013 Copyright Taylor and Francis Group, LLC.

Non-covalent chemistry of graphene: Electronic communication with dendronized perylene bisimides - Kozhemyakina, Nina; Englert, Jan; Yang, Guang; Spiecker, Erdmann; Schmidt, Cordula; Hauke, Frank; Hirsch, Andreas; Spiecker, Erdmann (Advanced Materials, 2010)
Mutual attraction: π-π bonding promotes electronic interactions between graphene and a π-conjugated perylene in a liquid dispersion. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.